2002
DOI: 10.4049/jimmunol.169.3.1219
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling-3 Is Recruited to the Activated Granulocyte-Colony Stimulating Factor Receptor and Modulates its Signal Transduction

Abstract: G-CSF is a polypeptide growth factor used in treatment following chemotherapy. G-CSF regulates granulopoiesis and acts on its target cells by inducing homodimerization of the G-CSFR, thereby activating intracellular signaling cascades. The G-CSFR encompasses four tyrosine motifs on its cytoplasmic tail that have been shown to recruit a number of regulatory proteins. Suppressor of cytokine signaling 3 (SOCS-3), also referred to as cytokine-inducible Src homolgy 2-containing protein 3, is a member of a recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
101
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(112 citation statements)
references
References 61 publications
9
101
1
1
Order By: Relevance
“…The strength of cytokine signals is regulated, in part, by a family of endogenous JAK kinase inhibitor proteins referred to as suppressors of cytokine signaling (SOCS), cytokine-inducible Src homology 2 (SH2) proteins (CIS), or STAT-induced STAT inhibitors (SSI) (3)(4)(5)(6)(7). Among these, SOCS3 is strongly induced by a variety of cytokines and other stimulations, including IL-6, IL-10, granulocyte-colony stimulating factor (G-CSF), EPO, EGF, leptin, and LPS (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Both SOCS1 and SOCS3 have an N-terminal kinase inhibitory region and inhibit JAK tyrosine kinase activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of cytokine signals is regulated, in part, by a family of endogenous JAK kinase inhibitor proteins referred to as suppressors of cytokine signaling (SOCS), cytokine-inducible Src homology 2 (SH2) proteins (CIS), or STAT-induced STAT inhibitors (SSI) (3)(4)(5)(6)(7). Among these, SOCS3 is strongly induced by a variety of cytokines and other stimulations, including IL-6, IL-10, granulocyte-colony stimulating factor (G-CSF), EPO, EGF, leptin, and LPS (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Both SOCS1 and SOCS3 have an N-terminal kinase inhibitory region and inhibit JAK tyrosine kinase activity.…”
mentioning
confidence: 99%
“…The G-CSF induces activation of the JAK-STAT (9,10,(15)(16)(17)(18) and the Ras-Raf-ERK pathways (18,19). Overexpression studies have suggested that SOCS3 interacts with the G-CSF receptor and inhibits G-CSFinduced STAT3 activation (9,20).…”
mentioning
confidence: 99%
“…SHP-1 and the suppressors of cytokine signaling (SOCS) protein SOCS3 have recently been implicated in negative regulation of G-CSFR signaling (15,16). SOCS proteins can inhibit cytokine signaling by directly binding to either Jak kinases or phosphotyrosine residues in the cytoplasmic domains of cytokine receptors to compete for binding with STAT molecules (17)(18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…Each of these modules contributes to attenuation of the duration and intensity of JAK-STAT signalling. The SH2 domain is responsible for SOCS3 binding to both the phosphotyrosine residues within cytoplasmic domain of the receptor and JAK kinase following cytokine-mediated activation (Dunn et al 2005;Hortner et al 2002a;Hortner et al 2002b;Nicholson et al 2000;Sasaki et al 1999). As a consequence, SOCS3 is thought to inhibit signal transduction by directly inhibiting JAK activity through the kinase inhibitory region (KIR) located in the SOCS3 N-terminus .…”
Section: Introductionmentioning
confidence: 99%